Arctic migrants/Arctic villagers : the transformation of Inuit settlement in the central Arctic - Damas, David (McGill-Queen's native and northern series, 2002)
"In recent years the view has emerged that the Inuit were coerced by the Canadian government into abandoning life in scattered camps for centres of habitation. In Arctic Migrants/Arctic Villagers David Damas demonstrates that for many years government policies helped maintain dispersed settlement, but that eventually concerns over health, housing, and education and welfare brought about policy changes that inevitably led to centralization." "Damas shows that while there were cases of government-directed relocation to centres, centralization was largely voluntary as the Inuit accepted the advantages of village living. In examining archives, anthropological writings, and the results of field research from an anthropological perspective, Damas provides fresh insights into the policies and developments that led to the centralization of Inuit settlement during the 1950s and 1960s."--Jacket.